LEGALITAS HUKUM PERKAWINAN BEDA AGAMA DI INDONESIA - Zulfadhli Zulfadhli; Muksalmina Muksalmina (Jurnal Inovasi Penelitian, 2021)
Marriage law in Indonesia is based on religious norms as outlined in Article 2 paragraph (1). On the other hand, religion in Indonesia is plural in nature, to bring together two people with different beliefs to love each other cannot be avoided, besides that there is a religion that allows interfaith marriage and from the perspective of Human Rights (HAM) it is also prohibited to prohibit humans from forming a family. . Seeing the fact that there is an increasing number of different marriage partners both domestically and abroad. This writing aims to examine how the strength of marriage law in Indonesia. This research is a normative legal research through a qualitative approach which is carried out by first examining written laws and regulations established by state institutions or authorized and generally binding officials. The specification of this research is analytical prescriptive. The data collection technique used in this research is library research and the analysis used is normative qualitative analysis. The results of research on interfaith marriages against Muslims both domestically and abroad do not have legal legality, because there is no term civil marriage as adopted by Protestant Christianity.